2021
DOI: 10.1177/10732748211036057
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ Perceptions About Cancer and Preferences for Cancer Education

Abstract: Background Cancer is one of the leading causes of death within the United States. Adolescence remains a critical stage of development in which new cognitive skills and lifestyle factors related to cancer are acquired. It is critical to understand adolescents’ knowledge of cancer and preferences for receiving clear and easy-to-comprehend information about cancer and cancer prevention. The purpose of this study was to explore adolescents’ perceptions of cancer and cancer risk factors and identify their preferenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 53 publications
3
8
0
Order By: Relevance
“…The sun exposition was identified in 23.1% and only 1.2% trauma as risk factors. These results bring us an alert that knowledge about relevant risk factors is not of a broad domain in this age group, consistent with previous studies that also identified a lack of knowledge of risk factors [17][18][19][20][21][22]24 .…”
Section: Miscellaneoussupporting
confidence: 91%
See 1 more Smart Citation
“…The sun exposition was identified in 23.1% and only 1.2% trauma as risk factors. These results bring us an alert that knowledge about relevant risk factors is not of a broad domain in this age group, consistent with previous studies that also identified a lack of knowledge of risk factors [17][18][19][20][21][22]24 .…”
Section: Miscellaneoussupporting
confidence: 91%
“…32.9% of these students reported still not learning anything about this topic. Abraham et al 24 reported in their study on the perception of adolescents about cancer and education preferences, the importance of developing strategies for teaching the topic among this age group, and how much the change in this teaching pattern can impact the level of knowledge and disease control, which is in line with the suggestions of the interviewees in this study (talking to specialists, video classes, practical classes, among others).…”
Section: Miscellaneoussupporting
confidence: 83%
“…Data were collected from at least 140 students per school from 17 schools, resulting in a total of 2400 participants. The mean age of participants was 17.32 years (SD = 1.22; range [16][17][18][19][20][21][22][23][24], more than 70% of students belonged to the Akan tribe and 46% were in SHS level one. The majority (70%) of students were boarders, and 55% were enrolled in General/Visual Arts.…”
Section: Resultsmentioning
confidence: 99%
“…A qualitative study involving twenty five focus groups of high school students, found that the most preferred sources, settings and medium of cancer education were health experts and cancer survivors, schools and online videos, and face-to-face presentations respectively [ 19 ]. A quantitative study of 233 high school students reported that over 85% preferred educational games for learning about cancer [ 20 ]. Surprisingly, while online resources were highly endorsed in these studies, students identified it as a potential source of misinformation [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In another study, which did not meet inclusion criteria, Lana et al (2013) created a website with games, videos, links, and a discussion forum about multiple cancer risk factors. Internet- or app-based education, especially game-based methods, has the potential to empower adolescents to reduce cancer risk (Abraham et al, 2021). Adolescents spend an increasing amount of time online; in 2018, 95% of U.S. adolescents had access to smartphones and 88% to a home computer (Anderson & Jiang, 2018).…”
Section: Discussionmentioning
confidence: 99%